Study of the effects of process parameters on electroforced sedimentation in solid–liquid separation using response surface methodology - Alam, Md. Monjurul; Alam, Md Zahangir; Jami, Mohammed Saedi; Amosa, Mutiu K.; Iwata, Masashi (Springer Netherlands, 2016)
Electroforced sedimentation (EFS) is a wellknown technique for enhancing the solid content of the final sludge cake. However, the parameters affecting the performance of EFS and quality of the resulting sludge cake, as well as the removed water, are not sufficiently studied. In this research, a mixture of zinc oxide (representing sludge) and polyacrylamide (dewatering aid) were used as experimental materials. The process parameters of electroforced sedimentation were optimized using a design of experiment software (Design Expert Version 7.0.0) with a face-centered central composite design (FCCCD) under response surface methodology. An optimization study was carried out for the output response (sedimentation velocity) based on three process factors and an empirical model was developed. The optimized values for current density, total solid volume per unit cross-sectional area and polyacrylamide dose for the highest sedimentation velocity (0.0199 cm/min) were 6.0 A/m2 , 7.74 mm and 1.53 % (based on the weight of zinc oxide), respectively. The overall model was significant with Prob [F value of 0.0117 and R2 value of 0.8911 while the most significant parameter was observed to be the current density with a Prob [F value of 0.0004. Validation experiments were conducted to confirm and measure the accuracy of the models for the three set of parameters including optimum parameters. The error was within the limit of prediction accuracy, and the sedimentation velocity was enhanced by the addition of 1.53 % PAM as dewatering aid. Thus, it was concluded that EFS can be applied successfully for materials having permanent charge.